Design of newly effective grain refiner for aluminum based on medium-entropy metal diboride. (November 2022) - Xiao, Fei; Wu, Mingxu; Wang, Yixiao; Wang, Shubin; Shu, Da; Wang, Donghong; Zhu, Guoliang; Mi, Jiawei; Sun, Baode
Abstract: In this paper, medium-entropy metal diboride (Ti1/3 Cr1/3 V1/3 )B2 with a hexagonal TiB2 -type crystal structure were synthesized via molten salt reaction, and its effect on refining pure aluminum grains was investigated. Compared with TiB2, the minimum lattice mismatch between Al and (Ti1/3 Cr1/3 V1/3 )B2 is reduced from 5.6% to 3.7%, effectively reducing undercooling required for nucleation. By just adding 1.5 vol% (Ti1/3 Cr1/3 V1/3 )B2, the average grain size of commercial pure aluminum is reduced to ∼32 μm. The synthesized particles are expected to be used in grain refinement during additive manufacturing and rapid solidification, and in the preparation of aluminum matrix composites. This study opens up a new direction in designing new compounds for grain refinement by tailoring lattice matching within multi-component composition space. Highlights: Medium-entropy (Ti1/3 V1/3 Cr1/3 )B2 particles refiners for CP-Al were synthesized by a molten salt reaction method. The refining ability of (Ti1/3 V1/3 Cr1/3 )B2 is better than TiB2 in CP-Al due to lower lattice disregistry between (Ti1/3 V1/3 Cr1/3 )B2 and Al. The refiner design in multiprincipal component space enable the lattice mismatch between particles and Al matrix is controllable.